Europejski Zielony Ład – cele, zobowiązania oraz reakcje społeczne i polityczne w Polsce .......... 29 - Królczyk, Barbara (Drill, baby, drill! Wykorzystanie zmian klimatu i ochrony środowiska w celach politycznych, 2025)
The article analyzes the European Green Deal (EGD) as a key climate and energy strategy of the European Union, aimed at achieving climate neutrality by 2050. The author presents the main objectives of the EGD, its institutional and legal framework, and the strategic documents associated with it. Particular attention is paid to assessing Poland’s position on the energy transition resulting from the EGD. The article highlights that although Poland formally supports the EGD’s goals, the implementation of climate policy faces significant challenges due to the country’s socio-economic conditions and the structure of its energy mix. The analysis reveals deeper tensions between EU-wide and national climate policies, as well as the challenges facing the Polish energy sector in the context of the transition.